Potential Synergies of β-Hydroxybutyrate and Butyrate on the Modulation of Metabolism, Inflammation, Cognition, and General Health - Franco Cavaleri; Emran Bashar (Journal of Nutrition and Metabolism)
The low-carbohydrate high-fat diet (LCHFD), also known as the ketogenic diet, has cycled in and out of popularity for decades as a therapeutic program to treat metabolic syndrome, weight mismanagement, and drug-resistant disorders as complex as epilepsy, cancer, dementia, and depression. Despite the benefits of this diet, health care professionals still question its safety due to the elevated serum ketones it induces and the limited dietary fiber. To compound the controversy, patient compliance with the program is poor due to the restrictive nature of the diet and symptoms related to energy deficit and gastrointestinal adversity during the introductory and energy substrate transition phase of the diet. The studies presented here demonstrate safety and efficacy of the diet including the scientific support and rationale for the administration of exogenous ketone bodies and ketone sources as a complement to the restrictive dietary protocol or as an alternative to the diet. This review also highlights the synergy provided by exogenous ketone, β-hydroxybutyrate (BHB), accompanied by the short chain fatty acid, butyrate (BA) in the context of cellular and physiological outcomes. More work is needed to unveil the molecular mechanisms by which this program provides health benefits.